The Role of Teachers in Handling Bullying Among Children in Kindergarten Learning Environments - indriyani Indriyani; Sadaruddin Sadaruddin; Andi Rezky Nurhidaya (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Bullying in early childhood represents a severe threat to the integrity of social-emotional development within the school environment. This study aims to analyze the manifestations of child bullying behavior in the learning environment of Pabata Ummi Kindergarten, as well as to evaluate the operationalization of teachers' strategic roles in detecting and intervening in such cases. A qualitative approach with a descriptive method was applied in this research. Data were gathered through a one-month passive participant observation, semi-structured in-depth interviews with the principal, classroom teacher, and parents, along with a documentary review of children's developmental anecdotal records. Data analysis was conducted interactively, encompassing data reduction, thematic data display, and conclusion drawing. The results indicated that physical bullying (pushing, seizing items), verbal bullying (mocking parents' names, taunting peers' abilities), and relational bullying (social exclusion from playgroups) still frequently occurred, particularly during free-play hours due to limited daily supervision ratios. Educators play a vital role as counselors, facilitators, and motivators by implementing a conducive classroom environment and executing humanistic, non-violent, curative-restorative measures. Nevertheless, teacher interventions remain reactive-spontaneous based on personal empirical experience, due to the absence of standard operational guidelines at school and a lack of formal competency training. This study recommends the importance of strengthening anti-bullying conceptual literacy for educators through continuous workshops, alongside the necessity of synchronous positive parenting synergy with parents to dismantle the normalization bias of childhood violence in order to establish a safe, inclusive, and child-friendly early childhood education unit.